EMOTIONAL INTELLIGENCE AS THE MOST SIGNIFICANT FACTOR TO DETECT AND MANAGE EMOTIONS - Mirzoyan, V. Kh. (Modern Psychology, 2021)
In this article the emotional intelligence is considered as the most important factor in understanding and detecting not only our own, but also others’ emotions. High level of emotional intelligence helps to establish interpersonal relationship, regulate behavior and avoid conflicts. People with high level of EQ are more self-confident, flexible and concentrated. Emotions play a vital role in the person’s life, regulating his activities body state, mindset and behavior. They help us to orientate in the environment, realize our demands and aims to satisfy, reach our destination. Emotions motivate us to do some actions, make decisions and understand others’ emotions. A research has been conducted with students in order to determine the level of emotional intelligence, as well as to find out the emotions that are most easily recognized.
Keywords: emotional intelligence, emotion, emotion management, emotion recognition, manipulation.